(untitled) (Leadership, Education, Personality: An Interdisciplinary Journal, ISSN: 2524-6178, 2024)
Strategic management encompasses a broad range of activities aimed at steering an organization towards its long-term goals. It is a continuous process of planning, execution, and evaluation, requiring a deep understanding of both internal capabilities and external market conditions. This study aims to offer a thorough examination of the various aspects of strategic management with special reference to HDFC Bank. By blending descriptive and analytical approaches and employing a robust mixed-methods research design, the study seeks to provide actionable insights and recommendations for enhancing strategic management practices in the banking sector.